2014
DOI: 10.1017/s1041610214000763
|View full text |Cite
|
Sign up to set email alerts
|

Charles Bonnet syndrome and cognitive impairment: a systematic review

Abstract: Background: Charles Bonnet syndrome (CBS) is defined as complex persistent visual hallucinations in the absence of mental disorder. It is common in conditions causing significant visual impairment. Many authors advise reassurance, considering the condition benign. However, others have suggested that CBS may in some patients represent the early stages of dementia. This review seeks to systematically examine the evidence for any link between CBS and cognitive impairment. Methods: Literature search using OVID Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
10
0
3
Order By: Relevance
“…86 Some patients presenting with Charles Bonnet syndrome to ophthalmology clinics may have unrecognised dementia characterised by partial or fluctuating insight into VH. 87 Case report evidence suggests that optimising vision may help reduce VH in dementia. 88…”
Section: Comorbid Diseasementioning
confidence: 99%
“…86 Some patients presenting with Charles Bonnet syndrome to ophthalmology clinics may have unrecognised dementia characterised by partial or fluctuating insight into VH. 87 Case report evidence suggests that optimising vision may help reduce VH in dementia. 88…”
Section: Comorbid Diseasementioning
confidence: 99%
“…Psikiyatrik bozukluk veya nörolojik lezyon/anormallik bulgusu olmayan görme engelli bireylerde sürekli veya periyodik kompleks görme varsanýlarý; CBS olarak tanýmlanmýþtýr (11). CBS'li hastalar tarafýndan tariflenen görme varsanýlarý; basit veya karmaþýk olabilir veya basit baþlayýp karmaþýk hale dönebilir (12).…”
Section: öZetunclassified
“…Varsanýlar renkli, sabit, hareketli veya görme alaný içinde hareket ediyor olabilir; bazý hastalarda her zaman ayný varsaný görülebilir (13). Yazarlar; demans veya görme varsanýlarýna neden olduðu bilinen diðer koþullarýn varlýðýnda CBS tanýsýnýn konulmamasý konusunda hemfikirdir (11). Nitekim bu olguda da, görme varsanýlarýný açýklayacak herhangi bir nörobiliþsel ya da psikiyatrik bozukluk tespit edilememiþtir.…”
Section: öZetunclassified
“…The study was not able to report a positive result on its primary outcome, whether there was a difference in the rate of conversion to dementia between the two groups. However, the finding that two patients diagnosed with CBS went on to develop dementia is a useful addition to the existing literature in the area, which is mostly in the form of case reports (Russell and Burns, 2014). The secondary outcome of the study was to determine whether there were deficits on cognitive testing in the CBS group.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Patients with CBS are often reassured that their symptoms do not signify the presence of a serious mental disorder (Norton‐Willson and Munir, ; Menon et al ., ; Hedges, ; Crumbliss et al ., ). However, a systematic review of the literature relating to the relationship between CBS and cognitive impairment (Russell and Burns, ) found that there was no reliable evidence on which to base these reassurances. The studies which have explored this relationship have used measures of cognitive function that are likely to have been insufficiently sensitive to rule out the presence of significant impairment, or have had methodological weaknesses.…”
Section: Introductionmentioning
confidence: 99%